Due Process in the United Nations. Issue 1 (January 2016) - Hovell, Devika
Abstract : "For hard it is for high and stately buildings long to stand except they be upholden and staid by most strong shores, and rest upon most sure foundations" —Jean Bodin, The Six Books of a Commonweale (1576) It has been said of the redemptive quality of procedural reform that it is "about nine parts myth and one part coconut oil." Yet, as the recent history of the United Nations shows, failure to enact adequate procedural reform can have damaging consequences for an organization and its activities. In the targeted-sanctions context, litigation in over thirty national and regional courts over due process deficiencies has had a "significant impact on the regime, " placing it "at a legal crossroads." In the peacekeeping context, the United Nations' position that claims in the ongoing Haiti cholera controversy are "not receivable" has been described in extensive and uniformly critical press coverage as the United Nations' "Watergate, except with far fewer consequences for the people responsible." Complacency in the face of allegations of sexual abuse by UN blue helmets led to the unprecedented ousting of a special representative to the secretary-general in the Central African Republic. Economizing on due process standards is proving to be a false economy.